PENEGAKAN HUKUM YANG BERKEADILAN TERHADAP HUKUMAN TAMBAHAN KEBIRI KIMIA (STUDI KASUS PERKARA NOMOR 2627/PID.SUS/2019/PN SBY) - Ferdinand Sujanto (The Juris, 2020)
This research was conducted based on the objective of assessing the effectiveness of just law enforcement on the application of additional chemical castration penalties. The application of additional chemical castration punishment has been included in one of the cases, namely registered with case number 2627/Pid.Sus/2019/PN Sby. The research method used by the author is a normative juridical research. The research approach undertaken by the author is literature study, statutory study, and case study. In addition, this study uses various legal materials, namely primary legal materials consisting of copies of case decisions 2627/Pid.Sus/2019/PN Sby, secondary legal materials consisting of a collection of journals and books, as well as tertiary legal materials consisting of sources Internet. This study uses deductive analysis techniques as the main support. The findings in this study basically state that there was an error in the application of the law in the case 2627/Pid.Sus/2019/PN Sby which resulted in not achieving just law enforcement. So that the result of not achieving the essence of fair law enforcement makes the application of additional chemical castration punishment unable to answer the problem of sexual crimes against children which have a deterrent effect.